2006
DOI: 10.1042/bj20060437
|View full text |Cite
|
Sign up to set email alerts
|

A novel locust (Schistocerca gregaria) serine protease inhibitor with a high affinity for neutrophil elastase

Abstract: We have purified to homogeneity two forms of a new serine protease inhibitor specific for elastase/chymotrypsin from the ovary gland of the desert locust Schistocerca gregaria. This protein, greglin, has 83 amino acid residues and bears putative phosphorylation sites. Amino acid sequence alignments revealed no homology with pacifastin insect inhibitors and only a distant relationship with Kazal-type inhibitors. This was confirmed by computer-based structural studies. The most closely related homologue is a put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 47 publications
3
24
1
Order By: Relevance
“…Greglin, initially named for an antielastase protein isolated from S. gregaria ovaries (47), represents a novel member of nonclassic Kazal-type serine protease inhibitors targeting elastase and chymotrypsin. Previously, the function of Greglin has only been reported in S. gregaria, and its inhibitory activities have solely been determined by structural and biochemical analyses of purified Greglin protein (47,48). In the present study, we demonstrated that Greglin appeared to be specifically expressed in adult female locusts and was the third of the 3 most highly expressed genes, after 2 Vg genes.…”
Section: Discussionmentioning
confidence: 99%
“…Greglin, initially named for an antielastase protein isolated from S. gregaria ovaries (47), represents a novel member of nonclassic Kazal-type serine protease inhibitors targeting elastase and chymotrypsin. Previously, the function of Greglin has only been reported in S. gregaria, and its inhibitory activities have solely been determined by structural and biochemical analyses of purified Greglin protein (47,48). In the present study, we demonstrated that Greglin appeared to be specifically expressed in adult female locusts and was the third of the 3 most highly expressed genes, after 2 Vg genes.…”
Section: Discussionmentioning
confidence: 99%
“…Then the samples were added to preheated test tubes and incubated for 1 hour at temperatures from 25°C to 100°C [35]. The residual trypsin inhibitory activity of rSdPI peptide was determined by the method described above.…”
Section: Methodsmentioning
confidence: 99%
“…More recently work has been done on greglin, a novel locust serine protease inhibitor with a high affinity for NE [100]. This is a fast acting and tight binding inhibitor of human NE, which also binds neutrophil cathepsin G, pancreatic elastase and chymotrypsin with lower affinity.…”
Section: Other Naturally Occurring Antiproteasesmentioning
confidence: 99%